A retrospective observational study for the outcomes of women presenting to a colposcopy clinic with a high‐grade Pap smear – Implications for a 'see and treat' approach to management. (10th February 2016) - Blain, Gemma; Richards, Anthony; Pather, Selvan; Carter, Jonathan; Saidi, Sam
Abstract : Background: The current Australian National Health and Medical Research Council guidelines discourage the use of 'see and treat' colposcopic management due to concerns regarding over‐treatment. However, this approach has been shown to have benefits in several studies, including cost savings, elimination of loss to follow up and decreased patient anxiety. Aims: To provide Australian data on treatment outcomes for women presenting with a high‐grade Pap smear to a large metropolitan colposcopy unit and to determine whether a 'see and treat' approach would meet specified standards. Materials and methods: Retrospective review of women referred to the Royal Prince Alfred Hospital colposcopy unit with a high‐grade smear. Patient data, colposcopy findings, treatment and pathology results were collated and analysed to determine treatment outcomes using the current 'biopsy and treat' approach. The feasibility of 'see and treat' was assessed by determining which women with high‐grade colposcopy findings had high‐grade disease confirmed on biopsy or excisional specimens. Results: One hundred and thirty‐seven women underwent either excisional or ablative treatment. Of those undergoing excisional procedures, 81.3% had high‐grade dysplasia or invasive cancer, 11.6% had CIN1 and 7.1% had no dysplasia on histopathology. One hundred and twenty‐one with high‐grade colposcopy findings had histopathology results available. Using a 'see and treat' approach, 92.6% would have had confirmed dysplasia of any grade, while 91.7% had confirmed high‐grade dysplasia. Conclusions: 'See and treat' colposcopy is feasible in the Australian setting when applied to selected patients with high‐grade cytology and high‐grade colposcopic findings.